2018
DOI: 10.25182/jgp.2018.13.3.137-144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Galohgor Cookies and Powder Drinks on Visceral Adipose Tissue and Lipid Profile in Patients with Type 2 Diabetes Mellitus

Abstract: This study aimed to assess the intervention effect of cookies and galohgor powder drinks on visceral adipose tissue (VAT) and lipid profile in patients with type 2 diabetes mellitus. The study design was quasi experimental. Subjects of this study were 26 adults with type 2 diabetes mellitus in Bogor District, West Java. Subjects were divided into two intervention groups; cookies and galohgor powder drinks (GCPD) group and cookies and powder drinks without galohgor (CPD) group. Both interventions were given for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In an animal study, Leatemia (2010) reported that galohgor significantly increases endogenous antioxidant superoxide dismutase (SOD) and reduces malondialdehyde (MDA) plasma. In another study examining type 2 diabetes mellitus patients, nutraceutical galohgor was shown to reduce visceral fat and oxidative stress biomarkers (Setyaningsih et al, 2017; Damayati et al, 2018). However, despite various studies that indicate the potential effect of galohgor on diabetes treatment, the effect of galohgor consumption on levels of oxidative stress in postpartum mothers has not been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…In an animal study, Leatemia (2010) reported that galohgor significantly increases endogenous antioxidant superoxide dismutase (SOD) and reduces malondialdehyde (MDA) plasma. In another study examining type 2 diabetes mellitus patients, nutraceutical galohgor was shown to reduce visceral fat and oxidative stress biomarkers (Setyaningsih et al, 2017; Damayati et al, 2018). However, despite various studies that indicate the potential effect of galohgor on diabetes treatment, the effect of galohgor consumption on levels of oxidative stress in postpartum mothers has not been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…IGF concentration significantly decreased in the control group, whereas it could be maintained in the intervention group during postpartum (Table 3). Galohgor has long been used by postpartum mothers in the Sundanese community 16 . Several studies have scientifically proven the benefits of galohgor for postpartum mothers 16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…Galohgor has long been used by postpartum mothers in the Sundanese community 16 . Several studies have scientifically proven the benefits of galohgor for postpartum mothers 16,17 . This study supports those scientific evidences whereas Galohgor cookies appeared to be able to support the growth of newborns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations